Handheld ECG Tracking of in-hOspital Atrial Fibrillation (HECTO-AF): A Randomized Controlled Trial - Mancinetti, Marco; Schukraft, Sara; Faucherre, Yannick; Cook, Stéphane; Arroyo, Diego; Puricel, Serban (Frontiers in Cardiovascular Medicine, 2021)
Background: Atrial fibrillation (AF) is frequent and causes substantial morbidity through AF-related strokes. Given the increasing prevalence of AF, screening methods are of interest given the potential to initiate timely appropriate anticoagulation. Aims: The HECTO-AF trial aims to determine the efficacy of AF screening with a single-lead electrocardiogram (ECG) handheld device in naïve in-hospital patients. Methods: The HECTO-AF is a single-center, open label, randomized controlled trial. Patients admitted to the general internal medicine ward of the University and Hospital Fribourg without previous diagnosis of AF were invited to participate in a screening program with a 1:1 allocation to either the screening group with intermittent single-lead handheld ECG recordings vs. a control group undergoing detection of AF as per routine clinical practice. The primary outcome was the prevalence of newly diagnosed AF during the hospital stay. Enrolment was terminated for poor patient recruitment and apparent futility before a sufficient sample for powered efficacy comparisons was enrolled. Results: A total of 804 patients were included of whom 381 were allocated to the intervention and 423 to the control group. Mean age was 65 ± 16 and 464 (58%) were male. Median CHA2DS2-VASc score was 3 (13% heart failure, 57% hypertension, 19% diabetes mellitus, 14% prior stroke/transient ischemic attack, and 29% arterial disease) and all CHA2DS2-VASc risk factors were equally distributed between groups. The incidence of newly detected AF was 1.4% over a median of 6 hospitalized days. Seven patients (1.8%) were diagnosed with AF in the intervention group vs. 3 (0.7%) in the control group (p = 0.20). Conclusion: There was a trend toward a higher AF detection over a median of 6 hospitalized days in the intervention group, but a definitive conclusion cannot be drawn due to the early termination of the present study. Systematic screening for AF in the hospital setting is resource-consuming, and of uncertain clinical benefit. The interpretation of single-lead handheld ECG is challenging and may result in inaccurate AF diagnosis. Clinical Trial Registration:ClinicalTrials.gov, identifier [NCT03197090].